Sustainable Building Users Satisfaction: Evidence From University Building In Yola-Nigeria - Lelle, Hyluwa; Jimoh, Richard; Oyewobi, Luqman; Bilau, Abdulquadir; Ibrahim, Kabir (UI Scholars Hub, 2020)
The quest for sustainable development has placed universities in the central role of sustainability in teaching, research, and application of sustainable principles in the development of their assets. To this end, there was the development of sustainable designs and structures out of many shipping containers within the University environment based in Yola-Nigeria. This study evaluated the satisfaction and comfort of users of the administrative office building through post-occupancy evaluation. The Building Use Studies (BUS) method was adopted to evaluate the performance of the buildings. Data obtained were analysed using the descriptive method of analysis of the BUS survey. Findings show that some sustainable features necessary to ensure the performance of the building, provide comfort and enhance workers’ productivity are entrenched in the buildings. All the requisite variables necessary to ensure satisfaction and comfort of the occupants/users of the Buildings are within or above the established benchmark. The lack of personal control of some key variables such as thermal comfort in the physical surrounding is noted to affect some users.